Front Cover: Copper(I) and Gold(I) Complexes of Aminofunctionalized Phosphinines: Synthesis and Structural Characterization (Z. Anorg. Allg. Chem. 6‐7/2023). Issue 6 (3rd April 2023) - Lin, Jinxiong; Frost, Daniel S.; Coles, Nathan T.; Weber, Manuela; Müller, Christian
Abstract : The cover picture shows the solid‐state structure of an unusual Cu4 ‐rhombus, which is capped by a total of four chlorido ligands. Two aminofunctionalized, aromatic phosphinines coordinate in the classical σ‐coordination mode via the phosphorus lone pair to two of the four Cu(I) centers. The other two phosphinines show a rare bridging μ2 ‐coordination mode and span two of the four Cu(I) centers. (DOI: 10.1002/zaac.202200365 ).